Cold War democracy the United States and Japan - Miller, Jennifer M. (Harvard University Press, 2019)
During the occupation American policymakers identified elections and education as the wellsprings of a democratic consciousness in Japan. But as the extent of Japan's economic recovery became clear, they placed prosperity at the core of a revised vision for their new ally's future, as Jennifer Miller shows in this fresh appraisal of the Cold War